FPGA Implementation and performance analysis of MUSIC algorithm for microphone array - Teologo, Antipas T., Jr. (Animo Repository, 2016)
This study presents an implementation in the field programmable gate array (FPGA) and performance analysis of the multiple signal classification (MUSIC) algorithm for the direction-of-arrival (DOA) estimation of the different sound sources. DOA offers a variety of applications in the field of signal detection, communications, navigation and speech processing. MUSIC is one of the high-resolution DOA estimation techniques and the most promising technique for actual hardware implementation. An antenna array consisting of four equally-spaced microphones (sensors) is used as a basis for this study. As for wideband application, the number of sources should be less than the number of sensors thus a maximum of three sound sources are only considered and their locations are estimated. Four DOAs are used for single-source, two sets of DOA for double-source and one set for triple source. Matlab simulations and testbench results are presented showing the effectiveness of the algorithm. All simulations and tests are done using five samples only because of the large logic utilization of the codes when comes to the FPGA implementation. This study utilizes an Altera Stratix II FPGA board for the realization of the MUSIC algorithm in hardware implementation and Verilog HDL serves as the programming language.